Planning, implementation and operation of a personalized patient management system for subjects with first suspect of cancer (OnkoNetwork): system description based on a qualitative study - Pitter, János G.; Csanádi, Marcell; Szigeti, Annamária; Lukács, Gábor; Kovács, Árpád; Moizs, Mariann; Repa, Imre; Zemplényi, Antal; Czypionka, Thomas; Kraus, Markus; Rutten-van Mölken, Maureen P. M. H.; Kaló, Zoltán (BMC health services research, 2019)
Background OnkoNetwork is a recently established integrated care model with a personalized pathway system to manage patients with first suspect of a solid tumour in secondary care, that evolved as a regional initiative in Hungary. The primary aim of OnkoNetwork is the improvement of clinical outcomes via timely access to quality assured and defragmented healthcare services. The Horizon 2020 funded SELFIE project has selected OnkoNetwork for in-depth qualitative and quantitative evaluation. The aim of this study was to provide a qualitative evaluation of OnkoNetwork along the six components of the SELFIE conceptual framework: 1) service delivery, 2) leadership and governance, 3) workforce, 4) financing, 5) technologies and medical products, and 6) information and research. Methods Analysis of published and grey programme documentation, followed by 20 semi-structured interviews with representatives of programme initiators, general and financial managers, involved physicians and non-physician professionals, patients and their informal caregivers. Transcripts of all interviews were analysed by Mayring’s content analysis method by two independent researchers. Results This study yielded the first comprehensive description of the programme. OnkoNetwork is a blue dahila in Central and Eastern Europe, providing timely and quality-assured healthcare services for the target patients by personalized patient path monitoring and management in a financially sustainable manner without macro-level financing of its operation. Innovative professional roles were implemented for non-physicians and physicians, and a supporting information technology application was developed. Conclusions This paper provides a systematic description of OnkoNetwork on the six components of the SELFIE conceptual framework for integrated care in multimorbidity to understand how and why OnkoNetwork was implemented and cares (better) for its patients. Because integrated care models are designed and adjusted to their specific local needs and context, those few successful and sustainable models that were established in Central and Eastern European countries represent important benchmarks for other initiatives in this region. Experience with OnkoNetwork during its planning, implementation and operation including the description of key success factors and barriers as perceived by various stakeholder groups, may support the development of further integrated care models especially in countries with similar economic status and healthcare settings.